The Economic Status of People with Disabilities and Their Families since the Great Recession - Leila Bengali; Mary C. Daly; Olivia Lofton; Robert G. Valletta (Institute of Labor Economics (IZA), 2021)
People with disabilities face substantial barriers to sustained employment and stable, adequate income. We assess how they and their families fared during the long economic expansion that followed the Great Recession of 2007-09, using data from the monthly Current Population Survey (CPS) and the March CPS annual income supplement. We find that the expansion bolstered the well-being of people with disabilities and in particular their relative labor market engagement. We also find that applications and awards for federal disability benefits fell during the expansion. On balance, our results suggest that sustained economic growth can bolster the labor market engagement of people with disabilities and potentially reduce their reliance on disability benefits.
Keywords: J14; J11; J18; 330; disability; employment; income; program participation